Determinasi Audit Delay Pada Perusahaan Manufaktur Di Indonesia Periode Pandemi Covid-19 - Istamar Istamar; Rochmad Bayu Utomo (Peneliti.net, 2023)
Audit delay is the length of time for audit completion as measured from the closing date of the company's books until the date the financial statements are issued. This study aims to examine the effect of auditor quality, opinion and auditor turnover on audit delay. One of them happened to manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. There were 44 research samples using purposive sampling method. The analysis technique used in this study is Multiple Linear Regression. The results of the study show that (1) auditor switching has no effect on audit delay, (2) auditor opinion has an effect on audit delay, and (3) auditor quality has no effect on audit delay.